Correlation detachment coffee force fruit under different conditions nutrition - da Silva, Flávio Castro; da Silva, Fábio Moreira; Scalco, Myriane Stella; Sales, Ronan Souza (Coffee Science - ISSN 1984-3909, 2016)
The coffee yield is strongly influenced by adequate supply of water and nutrients to plants. Because not all soil is the ideal amount of nutrients for plant growth, fertilization is intended to supplement these nutrients. The nole of fertigation is to provide coffee the water volume to be supplied with nutrients and preventing entering the plant water stress and nutrition. This study was carried out in the experimental area of the Department of Agriculture, Universidade Federal de Lavras in coffee cultivar Catigua MG 3 plants spaced 2.5 x 0.60 m. We tried to raise the detachment force of fruit maturation in green and cherry fruit moisture, trying to verify if these parameters correlate with the status of plants, over the period of maturation and consequently the selective mechanical harvesting. It was concluded that the oscillations of the detachment force of the coffee cherry are related to variables of the soil. The alterations found in fruit detachment force are observed when changes occur in soil moisture and soil water tension.